REGENERASI LEMPUNG BENTONIT DENGAN NH4+ JENUH YANG DIAKTIVASI PANAS DAN DAYA ADSORPSINYA TERHADAP Cr(III) - Emmy Sahara (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2011)
This paper discusses the adsorption capacity of bentonite clay to Cr (III) which was previously regenerated with saturated NH4+ and heat activated. The clay regenerated was the clay that have been used for adsorption of Cr(III) in solutionIt was found that bentonite clay regenerated and heated at 150oC had the highest specific surface area and porous total volume which were 119.9632 m2/g and 107.3561 x 10-3 mL/g, respectively. The distribution of the porous size was bimodal, namely microporous and mesoporous, whereas the isotherm patern observed was classified as the L type. The highest surface acidity of 2.3644 mmol/g was showed by the clay that was heated at 350oC with active situs of 1.4238 x 1021 atom/g. The adsorption capacity of the clay increased with temperature. The highest adsorption capacity of 19.878 mg/g was shown by the clay that regenerated and activated at 150oC.